Crystal structure of di-μ-acetato-κ4O:O′-bis{(acetato-κ2O,O′)tetraaqua[1-(pyridin-2-ylmethylidene-κN)-2-(pyridin-2-yl-κN)hydrazine-κN1]lanthanum(III)} dinitrate hemihydrate - Mbossé Ndiaye-Gueye; Bocar Traoré; Ibrahima Elhadji Thiam; Ousmane Diouf; Emmanuel Wenger; Abdou Salam Sall; Claude Lecomte; Mohamed Gaye (Acta Crystallographica Section E: Crystallographic Communications)
In the binuclear title complex, [La2(C2H3O2)4(C11H10N4)(H2O)4](NO3)2·0.5H2O, the two lanthanum ions are nine coordinate in a distorted trigonal–prismatic geometry. Each LaIII ion is bonded to three N atoms of the Schiff base, 1-(pyridin-2-yl)-2-(pyridin-2-ylmethylene)hydrazine and is coordinated by one acetate group, which acts in η2-bidentate mode and two acetate groups that act in μ2-mode between the two LaIII ions. Two η1-water molecules complete the coordination sphere. All bond lengths in the coordination environment of the LaIII ion are slightly larger than those observed in the isostructural NdIII and SmIII complexes. The LaIII...LaIII distance is 4.6696 (6) Å. In the crystal, extensive O—H...O hydrogen-bonding interactions involving the coordinated water molecules and the non-coordinating nitrate anions, as well as the oxygen atoms of the acetate groups, generate an overall three-dimensional supramolecular network.